Preparation of New Azo-polyesters containing Chalcone Moiety in the main chain (Journal of Academic Research, 2023)
A series of four azopolyesters were synthesized by the interfacial Polycondensation technique of a chalcone diphenols; (E)-1،3-bis(4-hydroxyphenyl)prop-2-en-1-one I or(E)-3-(4-hydroxy-3-methoxyphenyl)-1(4hydroxyphenyl)prop-2-en-1-one II with diacid chlorides namely 3,3'-Azo dibenzoyl chloride III and 4,4'-Azo dibenzoyl chloride IV. Initially, the two chalcone moieties I, II were prepared by reacting two equivalents of 4-hydroxy benzylidene or 4-hydroxy-3-methoxy benzaldehyde with one equivalent of 4-Hydroxy acetophenone in the presence of a catalytic amount of concentrated HCl and EtOH as a solvent at reflux. The resulting azopolyesters were characterized by elemental analyses and IR spectroscopy.